Bioinspired surface functionalization of biodegradable mesoporous silica nanoparticles for enhanced lubrication and drug release - Xiaowei Mao; Kexin Chen; Yanlong Zhao; Chunrong Xiong; Jing Luo; Yuguang Wang; Bo Wang; Hongyu Zhang (Friction)
Abstract Osteoarthritis is associated with the significantly increased friction of the joint, which results in progressive and irreversible damage to the articular cartilage. A synergistic therapy integrating lubrication enhancement and drug delivery is recently proposed for the treatment of early-stage osteoarthritis. In the present study, bioinspired by the self-adhesion performance of mussels and super-lubrication property of articular cartilages, a biomimetic self-adhesive dopamine methacrylamide—poly(2-methacryloyloxyethyl phosphorylcholine) (DMA—MPC) copolymer was designed and synthesized via free radical polymerization. The copolymer was successfully modified onto the surface of biodegradable mesoporous silica nanoparticles (bMSNs) by the dip-coating method to prepare the dual-functional nanoparticles (bMSNs@DMA—MPC), which were evaluated using a series of surface characterizations including the transmission electron microscope (TEM), Fourier transform infrared (FTIR) spectrum, thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS), etc. The tribological test and in vitro drug release test demonstrated that the developed nanoparticles were endowed with improved lubrication performance and achieved the sustained release of an anti-inflammatory drug, i.e., diclofenac sodium (DS). In addition, the in vitro biodegradation test showed that the nanoparticles were almost completely biodegraded within 10 d. Furthermore, the dual-functional nanoparticles were biocompatible and effectively reduced the expression levels of two inflammation factors such as interleukin-1β (IL-1β) and interleukin-6 (IL-6). In summary, the surface functionalized nanoparticles with improved lubrication and local drug release can be applied as a potential intra-articularly injected biolubricant for synergistic treatment of early-stage osteoarthritis.